Reassembling academic work: a sociomaterial investigation of academic learning. Issue 3 (2nd September 2019) - Zukas, Miriam; Malcolm, Janice
ABSTRACT: Academic work is changing fast, as is the work of other professionals, because of challenges such as accountability and regulations frameworks and globalised academic markets. Such changes also have consequences for everyday academic practice and learning. This paper seeks to explore some of the ways in which academic work is changing by opening the 'black-box' of everyday academic work and examining the enactment of academics' everyday learning. The paper draws on a study of everyday academic practice in the social sciences with respect to the institution, the department and the discipline. Assuming a sociomaterial sensibility, the study also sought to understand how academics' learning is enacted in everyday work. Within three universities, fourteen academics were work-shadowed; social, material, technological, pedagogic and symbolic actors were observed and, where possible, connections and interactions were traced. The paper illuminates through two stories from the study how specific practices and meanings of disciplinary academic work are negotiated, configured and reconfigured within and beyond the department or meso-level, attending to resistance and rejection as well as accommodation and negotiation. The paper responds to educational concerns of professional (here, academic) learning by foregrounding both the assembling and reassembling of academic work and the enactment of learning.